'But do I care? No, I'm too old to care': authority, unfuckability, and creative freedom in Jane Campion's authorship after the age of sixty. Issue 2 (2nd September 2019) - Erhart, Julia
ABSTRACT: The twenty-first century has seen an increase in scholarly interest in the discursive construction of women film practitioners, yet much of this literature focusses on women at the younger- or middle-aged ends of the spectrum, leaving the positioning of older women directors unexamined. Taking Jane Campion as an important case study, this paper explores how Campion is depicted in critical discourses including journalistic responses from Cannes, comments by female industry peers, her self-construction in interviews, and via the television show Top of the Lake, with its unique focus on themes of women and aging. While there is consistency within each discourse in which Campion is situated, each emphasises different facets of Campion's career. This article explores counter-discourses around aging as uttered by Campion and as apparent in Top of the Lake and provides evidence of an intensified biographical focus in critical commentary from this stage of Campion's career. While not definitively attributable to Campion's biological age, the critical recourse to biography may be enabled by the sheer longevity of Campion's career and many decades in the public eye. Taken together, these constructions of 'Campion' are contradictory, however many succeed in putting pressure on hegemonic notions of gender and aging.